Development of gelatin nanoparticles conjugated with phytohemagglutinin erythroagglutinating loaded with gemcitabine for inducing apoptosis in non-small cell lung cancer cells. Issue 14 (21st March 2016) - Kuo, Wei-Ting; Huang, Jian-Yuan; Chen, Min-Hua; Chen, Ching-Yun; Shyong, Yan-Jye; Yen, Ko-Chung; Sun, Yu-Jun; Ke, Cherng-Jyh; Cheng, Yung-Hsin; Lin, Feng-Huei
Abstract : Fluorescent gelatin nanoparticles (GNPs) conjugated with PHA-E and carried gemcitabine were synthesized by nanoprecipitation for targeting and treatment of NSCLC cells. Abstract : Gelatin is an efficient drug delivery vehicle for attaching targeting molecules like phytohemagglutinin erythroagglutinating (PHA-E) and carrying the chemotherapeutic agent gemcitabine (GEM). Fluorescent gelatin nanoparticles (GNPs) conjugated with PHA-E and carrying gemcitabine (GNP–(PHA-E)–GEM) were synthesized by nanoprecipitation for guiding gemcitabine-loaded gelatin nanoparticles to NSCLC by PHA-E targeting. GNPs have a uniform narrow size distribution and spherical shape, and their particle size is about 290 nm. The release rate of gemcitabine from nanoparticles reached the plateau of the curve at approximately 30% within 72 hours. PHA-E conjugated nanoparticles could enhance the cellular accumulation of nanoparticles. The results showed that GNP–(PHA-E)–GEM treatment caused an increase of cell growth inhibition and cytotoxicity on NSCLC cells A-549 and H292. In an Annexin V/PI assay, treatment with GNP–(PHA-E)–GEM could induce apoptosis of cancer cells. Treatment of NSCLC cells with GNP–(PHA-E)–GEM firstly resulted in time-dependent inhibition of epidermal growth factor receptor (EGFR) and Akt phosphorylation. And it also could increase p53 phosphorylation. And then it could decrease Bad phosphorylation and increase Bax. Finally, it could result in enhancing the release of cytochrome c, which thus increases caspase-9 and caspase-3. In conclusion, GNP–(PHA-E)–GEM could induce growth inhibition and cytotoxicity, which was mediated through inhibition of EGFR phosphorylation and the switching on of p53 that causes cell apoptosis of NSCLC cells A-549 and H292. It's significant to conjugate PHA-E for targeting cancer and inhibiting EGFR phosphorylation as it could decrease the dosage of gemcitabine, which reduces side effects on normal tissue. GNP–(PHA-E)–GEM has great potential for NSCLC treatment.